ANALYTICAL EXAMINATION OF METHODS FOR MODELING BUSINESS PROCESSES IN E-COMMERCE - Shkil, R. A. (Science and Transport Progress, 2008)
In this article the theoretical aspects of modeling business-processes are considered, the characteristic of business modeling methods is given, their merits and demerits are determined, the comparative analysis of methods of modeling business-processes in e-commerce is performed.